ASUHAN KEPERAWATAN KELUARGA DENGAN RIWAYAT HIPERTENSI DI DUSUN GAYAMAN DESA GAYAMAN KECAMATAN MOJOANYAR KABUPATEN MOJOKERTO - Siti Rachmah, M.Kes; Rangga Kusuma P (MEDICA MAJAPAHIT, 2021)
Diabetic ulcers with gangrene are defined as necrotic tissue or dead tissue caused by the presence of large arterial blood vessel emboly on a part of the body so that the blood supply is stopped. The purpose of this study was to carry out wound care in diabetic patients with impaired skin integrity in Mojokerto. The results of study on participant i felt itchy around wounds, grade 1, red color 20% pink 60%, necrotic 20%, the outer side of the wound and around the wound was dry, located in the left lower limb. Participants 2 wound itchy, 60% red, 40% necrotic, grade 1, characteristic odor. Diagnosis obtained in participant 1 and participant 2 was damage to skin integrity associated with ulcers. Intervention and implementation were conducted on participant 1 in wound care with the principle of sterility and nutrition education. In participant 2 wound care with a sterile principle and faught to do foot exercises. With the results of participant is evaluation the condition of wound necrotic tissue was 5%, pink color was 95%, the edge of the wound was moist. Participant 2 conditions wes 10% necrotic tissue wound, dry wound. The evaluation obtained in participant 1 and participant 2 was partially resolved. It is expected that families and clients can maintain wound moisture and perform routine wound care.